A computational model for dilated cardiomyopathy: morphology and electromechanics - Athanasios, Andrew (AUC Knowledge Fountain, 2019)
The aim of this thesis was to develop a computational model that can simulate the key changes in morphology and electrophysiology that are observed in patients of dilated cardiomyopathy (DCM), and to predict the associated diastolic (mechanical) dysfunction. The computational model herein developed was then applied to an in-silico study of cardiac resynchronization therapy (CRT) to assess its potential utility as an investigative tool in clinical research. Specifically, the DCM model herein developed captures three beats of a human heart (male, in his mid-twenties). The case of DCM represented herein also possesses a left bundle branch block (LBBB). LBBB alters the sequence of electrical activation across the cardiac domain, leading to ventricular asynchrony and hampering cardiac systolic and diastolic functions, as is typical in DCM patients. A methodology for the cardiac growth and remodeling (morphing) was thus developed to represent the dilation of ventricles of DCM patients, based on an application of thermal expansion techniques. Then, a hierarchically coupled electromechanical model was set up to simulate the effect of DCM and LBBB on cardiac function. Predictions from our model were then compared to the literature and to clinical data that was made available to us by the Aswan Heart Centre (AHC) as part of a collaborative research project between the Magdi Yacoub Foundation (MYF) and the American University in Cairo (AUC). The computational platform used in this work is the SIMULIA Living Heart Human Model (LHHM), which is associated with the finite element solver ABAQUS. The LHHM is presently only available to members of the Living Heart Project (LHP). The proposed methodologies have fairly produced relevant models representing LBBB and DCM, which was successfully validated in comparison to the literature and to clinical data.